Comparative market study on milk powder brand in Bangladesh of Arla foods bd Ltd. - Mamon, Md.Abdullah Al (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2015.